Biological Age Associates with Longitudinal Frailty-Related Functional Decline: The Health and Retirement Study - Savvina Prapiadou; Tamara N Kimball; Benjamin Y Q Tan; Reinier W P Tack; Devanshi Choksi; Marie-Gabrielle Duperron; Jasper R Senff; Evy M Reinders; Tan Li Feng; Sanjula D Singh; Jonathan Rosand; Christopher D Anderson (The Journals of Gerontology, Series A: Biological Sciences and Medical Sciences, 2026)
Abstract Epigenetic clocks have emerged as markers of biological aging. Understanding their association with age-related functional decline may provide insights into DNA-mediated mechanisms underlying frailty-related functional decline and reveal which clocks best associate with accelerated functional decline. We therefore examined associations between established epigenetic clock measures and longitudinal trajectories of cognitive function, grip strength, and walking speed. We analyzed data from 4,018 participants in the Health and Retirement Study with available DNA methylation data and up to 12 years of follow-up data. Using linear mixed-effects models, we examined retrospective associations between twelve epigenetic clocks and longitudinal trajectories of frailty-related functional decline, modeling interactions between each epigenetic clock and time, adjusting for chronological age and sociodemographic covariates. In longitudinal analyses controlling for chronological age, older epigenetic age was associated with faster cognitive decline for Hannum (β = -0.0054, 95% CI: -0.0095, -0.0014, p = 0.009) and DNAmGrimAge (β = -0.0141, 95% CI: -0.0174, -0.0107, p < 0.001). Higher DNAmGrimAge was associated with accelerated decline in grip strength (β = -0.024, 95% CI: -0.033, -0.015, p < 0.001) and decline in walking speed (β = -0.0008, 95% CI: -0.0013, -0.0004, p < 0.001). Higher epigenetic clock biological age estimates, particularly DNAmGrimAge, are retrospectively associated with accelerated frailty-related functional decline across multiple functional domains. Systematic comparison of clock derivations may reveal specific epigenetic patterns underlying age-related functional deterioration.